Masalah pengajaran kemahiran berbahasa di sekolah di Indonesia - Sam Mukhtar Chaniago; Jamaludin Badusah; Mohamed Amin Embi (Penerbit UKM, 2011)
This concept paper discussing problems in lesson for four language skills that experienced by the students in their learning process at primary (SD), secondary (SMP) and high (SMA) school in Indonesia. These four problems are listening, reading, writing and speaking. Besides, there are also other problems experienced by the students in their learning process which requires the teacher as the arbitrator. Based on the theory discussed in this paper, it is expected that these problems could be overcome by the teachers. The teachers are able to achieve solutions that relevant to language learning growth at school